Pengaruh Gaya Kepemimpinan Dan Kompensasi Terhadap Turnover Intention Pada Hotel Sangga Buana - Wiludu, Bertha Mei; Apriadi, Deri (Pusat Riset dan Inovasi Nasional, 2025)
This study was conducted to evaluate the impact of leadership style and compensation on the tendency of employees to leave the job (turnover intention) in the work environment of Sangga Buana Hotel, located in Cipanas. This study uses a quantitative method with data collection through distributing questionnaires to the entire population of permanent employees, totalling 47 people. Data analysis was carried out using multiple linear regression techniques. The results of data processing show that the leadership style variable has a significant influence on employees' desire to leave the company, while the compensation variable does not show a significant influence. Together, the two factors were able to explain 44.1% of the variation that occurred in the turnover intention variable. This finding confirms that the role of effective and supportive leaders is key in reducing employee turnover intention in the hospitality sector.